How do students’ study habit and self-confidence affect their mathematics learning outcome? - Rahmawati, Afifah Sausan; Istihapsari, Vita (International Journal on Education Insight, 2021)
Study habits and self-confidence are several factors that are thought to be related to student mathematics learning outcomes. This research aims to determine whether there is a positive and significant relation between study habits and self-confidence to mathematics learning outcomes on the 11th grade students of SMA Negeri 1 Dukuhwaru, Indonesia. The type of this research is quantitative research. It involved 167 students of social sciences of SMA Negeri 1 Dukuhwaru. The instrument used was a test of learning outcomes and a questionnaire that had been tested for the validity and the reliability. Data analysis techniques used in this study are descriptive analysis, analysis prerequisite test, and hypothesis testing. The results of this study indicates that there is a positive and significant relation between study habits and self-confidence to mathematics learning outcomes on the 11th grade students of SMA Negeri 1 Dukuhwaru. It is indicated by   . Double correlation coefficients R = 0.547 dan  are 0.299 with    and SR(X1) = 62,63% and SR(X2) = 37,36%, SE(X1) = 18,74% and SE(X2) = 11,18%.